Image analysis of a tourist destination: Malaga, Spain - Almeida-García, Fernando; Domínguez-Azcue, Janire (My University, 2015)
The destination image is multidimensional in nature and the knowledge the individuals have of the destination and also their personal traits and opinions play an important role in it. Therefore, it is a complex construction in which the different information sources are decisive. Thus, the destination image plays a key role in both marketing and tourism location. The city of Malaga, located in Southern Spain, lies on the Costa del Sol (Coast of the Sun), a tourist area largely identified with seaside tourism. In recent years Malaga city has been trying to distance itself from the “sun and sand” tourism segment and it has chosen to position itself as a cultural destination (Diario Sur, 2014; The New York Times, 2015). In this regard, the effectiveness of the image of Malaga differentiated from a seaside destination image is analysed in the present study. The main objective of this research is to perform an analysis of the current image of the city and of the target one. A detailed study of the obtained results will enable us to take a close look at the tourists’ attitudes towards Malaga city and it will provide us with information to improve or design new differentiation strategies. This is the first academic study on Malaga’s destination image. Malaga is a Spanish municipality in Andalusia and it is located, as already mentioned, in the Costa del Sol, beside the Mediterranean Sea. The city had 566,913 inhabitants (2014) and an accommodation supply of 9,598 bed places and nearly one million of tourists (2013). We decided to focus the research on Malaga city, on the Costal del Sol, Spain, a traditionally touristic place which in the recent years is trying to specialize in urban and cultural tourism
Keywords: Turismo - Málaga; Imagen; Destino